Psychometric Properties of Brief Sensation Seeking Scale (BSSS-4) in a Sample of Turkish Adolescents - Eyüp Çelik (Sakarya University, 2015)
The purpose of the current research was to investigate the psychometric properties of the BSSS-4 in Turkish sample. In this study, firstly, the relationship between Turkish and English version was examined by Pearson Product-Moment Correlation for the linguistic equivalence. Exploratory factor analysis showed that four items loaded on single-factors as the factor structure of the original scale. The present study found that the Cronbach's Alpha coefficient of the scale is .81. These results demonstrated that the Turkish form of the Brief Sensation Seeking Scale for Adolescents is a valid and reliable instrument.